2015
DOI: 10.1186/s12955-015-0258-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of health-related quality of life in stroke patients after neurological inpatient rehabilitation: a prospective study

Abstract: BackgroundThe goal of the study was to investigate the long-term course of health-related quality of life (HRQoL) in stroke survivors during and up to 2.5 years after inpatient neurological rehabilitation and to identify predictors of HRQoL.MethodsHRQoL was determined in 152 stroke survivors in a single-centre prospective cohort study at four time points: upon admission to inpatient rehabilitation, at discharge, and one and 2.5 years after discharge. Their HRQoL was determined by administering the EQ-5D at all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 27 publications
6
67
0
1
Order By: Relevance
“…Adverse consequences on the physical, psychological, emotional, social, and economic status of stroke survivors place stroke among the leading causes of diminished quality of life globally [13]. Preventing stroke thus becomes a critical, better, and keenly sought after option.…”
Section: Introductionmentioning
confidence: 99%
“…Adverse consequences on the physical, psychological, emotional, social, and economic status of stroke survivors place stroke among the leading causes of diminished quality of life globally [13]. Preventing stroke thus becomes a critical, better, and keenly sought after option.…”
Section: Introductionmentioning
confidence: 99%
“…The studies investigating QoL in stroke mostly used generic health-related QoL tools, whereas studies using diseasespecific measurements for patients with stroke are scarce in the literature (Katona et al, 2015). This is especially the case in the Turkish population.…”
Section: Introductionmentioning
confidence: 99%
“…This would be in line with the fact that individuals who took part in MT assessed not only their current quality of life as higher but also their expected quality of life in the future, at the end of the therapy programme. And as shown by Katona's team (Katona et al, 2015), the higher the HRQL in stroke patients directly after release from hospital was, the higher were its levels one and 2.50 years later.…”
Section: Discussionmentioning
confidence: 98%
“…It is worth mentioning here the results of German research by Katona and colleagues, who suggested that the higher the HRQL directly after releasing patients from hospital after a stroke, the higher its levels are one and 2.50 years later (Katona, Schmidt, Schupp, & Graessel, 2015). In order to improve physical ability and, thus, improve the quality of life, physical therapy is used.…”
Section: Quality Of Life Post-stroke and Its Determinantsmentioning
confidence: 99%